Metabolite profiling of Scenedesmus regularis using Nuclear Magnetic Resonance (NMR) - Nyuk, Ling Ma; Teh, Kit Yinn; Aziz Ahmad,; Lam, Su Shiung; Shahidur Ashraf Saidon,; Mohd Naqiuddin Husri,; Cha, Thye San (Penerbit Universiti Kebangsaan Malaysia, 2019)
Metabolites represent the end product of gene function and it reflects direct response of cells under certain conditions. Hence, metabolite profiling has become a powerful tool in examination of plant cell’s response under certain conditions either in vitro or from tissue extract. This study aims to demonstrate how metabolite fingerprinting in microalgae in unfractionated extract. The results revealed the identification of 55 metabolites in unfractionated Scenedesmus regularis extract by using 1HNMR coupled with correlation spectroscopy (COSY).